Estimativa do volume de madeira para Eucalyptus sp. Com imagens de satélite de alta resolução espacial - DeMacedo, Fabrício Lopes; De Oliveira Sousa, Adélia Maria; Gonçalves, Ana Cristina; Silva, Hélio Ricardo [UNESP]; Rodrigues, Ricardo Antonio Ferreira [UNESP] (My University, 2017)
Volume estimates are particularly relevant in stands whose main production is wood. The objective of this study was to develop functions to estimate the total trade volume and with and without shell, with the help of high-resolution images for Eucalyptus. The allometric functions were adjusted from two sets of data: the volume estimated from the data of inventory plots and the mean value of vegetation index of a high spatial resolution image of the Pleiades satellite. The allometric functions with better performance for total and commercial volumes with and without bark are the ones with the Adjusted Vegetation Index for the Soil (SAVI) as an independent variable, with the adjusted coefficient of determination varying between 69 and 74%. These functions can be used not only at local and regional level, but also in regions with similar climate and local conditions and the same species of eucalyptus.
Wood volume estimates for Eucalyptus sp. With satellite images of high spatial resolution
Keywords: Allometric functions; Satellite pleiades; Vegetation indices